2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.107-309
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Different Coating for TiN Microelectrode Chambers Used for Neonatal Cardiomyocytes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The SNR for the platform was reported at 11.6 ± 0.5, which the authors reported as standard. Additional examples of ITO metallization for MEAs have been described in literature [99][100][101][102]. [129], with the inset depicting an unprocessed PET layer atop the PCB.…”
Section: Mea Substrates Conductors and Insulation Materialsmentioning
confidence: 99%
“…The SNR for the platform was reported at 11.6 ± 0.5, which the authors reported as standard. Additional examples of ITO metallization for MEAs have been described in literature [99][100][101][102]. [129], with the inset depicting an unprocessed PET layer atop the PCB.…”
Section: Mea Substrates Conductors and Insulation Materialsmentioning
confidence: 99%
“…The one hundred and twenty electrode 120MEA100/30iR-ITO-gr microelectrode chambers (Multi Channel Systems MCS GmbH) with 12×12 electrode layout ( Figure 1) were coated at 37 °C with 5 µg/ml (Sigma-Aldrich) fibronectin dissolved in 0.02% gelatin from bovine skin (Sigma-Aldrich) at least one hour before cell seeding. The MEA chambers were cleaned and sterilized before use as described earlier [4].…”
Section: Microelectrode Chambersmentioning
confidence: 99%
“…There are some disadvantages of MEA systems, such as complicated preparation of MEA chambers or difficult interpretation of results because of measuring the second signal derivation. The crucial step in MEA experiments is choosing the design of substrate-integrated microelectrodes and coating procedure depending on cell type [4].…”
Section: Introductionmentioning
confidence: 99%